Easy Access to a Cyclic Key Intermediate for the Synthesis of Trisporic Acids and Related Compounds (2014)
ABSTRACT: The synthesis of a cyclohexane skeleton possessing different oxygenated functional groups at C–3, C–8 and C–9, and a 1,6-double bond has been accomplished in 10 steps with an overall 17% yield. This compound is a key intermediate for access to a wide range of compounds of the bioactive trisporoid family. The synthetic sequence consists of the preparation of a properly functionalized epoxygeraniol derivative, and its subsequent stereoselective cyclization mediated by Ti(III). This last step implies a domino process that starts with a homolytic epoxide opening followed by a radical cyclization and regioselective elimination. This concerted process gives access to the cyclohexane moiety with stereochemical control of five of its six carbon atoms.